2018
DOI: 10.1080/21645515.2018.1534515
|View full text |Cite
|
Sign up to set email alerts
|

Primary care-based surveillance to estimate the proportion of rotavirus gastroenteritis among Latvian children below 5 years of age with acute gastroenteritis

Abstract: Background: Rotavirus (RV) is worldwide an important cause of acute gastroenteritis (AGE) in infants and young children. There is no specific treatment for AGE caused by RV (RVGE) but since 2006 two safe and effective vaccines have been available. RV vaccination was included in the national immunization program (NIP) of Latvia in 2015 with full reimbursement, and within the first year a coverage of 87% was achieved. This surveillance study was carried out to investigate the proportion of RVGE among AGE episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Moreover, this study also illustrates another finding, namely severe RV Vesikari score was found to be a significant risk factor for hospitalization. This report is in line with a recent study from Bulgaria, namely that both the RV‐status and the Vesikari score of the cases were independent risk factors for hospitalization 41 . Of particular interest in our cohort is the association identified with AGE disease severity and RVV.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, this study also illustrates another finding, namely severe RV Vesikari score was found to be a significant risk factor for hospitalization. This report is in line with a recent study from Bulgaria, namely that both the RV‐status and the Vesikari score of the cases were independent risk factors for hospitalization 41 . Of particular interest in our cohort is the association identified with AGE disease severity and RVV.…”
Section: Discussionsupporting
confidence: 91%
“…This report is in line with a recent study from Bulgaria, namely that both the RV-status and the Vesikari score of the cases were independent risk factors for hospitalization. 41 Of particular interest in our cohort is the association identified with AGE disease severity and RVV.…”
Section: Discussionmentioning
confidence: 99%
“…31,41 Heggie and colleagues describe the cost-impact of rotavirus immunization in Scotland 42 following the introduction of universal rotavirus immunization in 2013. In Latvia such a program was introduced only in 2015, a decision that was strengthened by the substantial disease burden of rotavirus gastroenteritis in Latvia, as demonstrated in this issue by Tafalla et al 43 The success of rotavirus vaccines in reducing the burden of diarrheal diseases opens new era toward the prevention of diarrheal diseases caused by other enteric viruses, such as norovirus. Indeed, there are currently several norovirus vaccines in clinical testing including an oral monovalent vaccine 44 and a bivalent vaccine given intramuscularly.…”
Section: Rotavirus Vaccinesmentioning
confidence: 99%